The Role of Islamic Law in Contemporary Constitutional Systems: Comparative Perspectives on Governance in Indonesia, Malaysia, Pakistan, and Egypt - Syed Agung Afandi; Naeem AllahRakha; Muslim Afandi; Rizki Erdayani; Nail Hidaya Afandi (Presscience, 2026)
This article explores the constitutional role of Islamic law (Sharia) within contemporary governance frameworks across four Muslim-majority states such as Indonesia, Malaysia, Pakistan, and Egypt. It argues that the interface between Sharia and constitutionalism represents an evolving negotiation of moral legitimacy, institutional design, and political power rather than a fixed dichotomy between secularism and theocracy. Using a comparative qualitative approach grounded in constitutional pluralism and governance legitimacy theory, the study analyzes constitutions, judicial decisions, and legislative instruments from 1945 to 2024. The findings identify three typological models of Islamic constitutional governance. The integrationist model, exemplified by Pakistan, embeds Sharia into the constitutional core through specialized courts and councils, reinforcing religious authority but limiting legislative autonomy. The dualist model, found in Malaysia, institutionalizes parallel jurisdictions between civil and Sharia courts, ensuring religious autonomy but perpetuating jurisdictional uncertainty. The contextual-adaptive model, as in Indonesia, integrates Sharia through decentralization and judicial review, balancing local autonomy and national oversight. Egypt, meanwhile, represents a hybrid statist model, where state institutions monopolize religious interpretation to maintain regime legitimacy. Comparative analysis reveals that constitutional trajectories depend less on religious doctrine than on the interplay of judicial independence, political coalitions, and decentralization. When Sharia interpretation aligns with maqāṣid al-sharī‘ah and human rights principles, it strengthens democratic legitimacy and legal pluralism. The article concludes by proposing a contextual constitutionalism model, offering an institutional framework for reconciling divine authority with constitutional democracy in Muslim-majority societies.